Sound effect of transmitting specific emotions in music performance based on the acoustic properties of conjugated materials - Li, Yangjingyi; Lee, Fenghsu (Frontiers in Chemistry, 2023)
In music performances, instruments made of traditional materials often cannot accurately express specific emotions through means such as tone, pitch, and timbre, and it is difficult to adjust the sound effects according to specific emotions. This article studies the impact of conjugated materials on the timbre, frequency response, etc. of musical instruments, hoping to achieve sound effects that better convey specific emotions. This article analyzes the acoustic properties of conjugated materials and applies them to musical performances. It is found that conjugated materials can provide a wider selection of tones, pitches and timbres, performers can choose appropriate tone, pitch, and timbre from conjugated materials to express emotions according to specific emotional needs, or adjust and transform the tone, pitch, and timbre for specific emotions, thereby arousing emotional resonance from the audience, so that specific emotions can be conveyed to the audience more accurately and powerfully. At the same time, this research also found that compared with an environment with poor sound insulation, the average sound absorption coefficient of metal materials in a room with good sound insulation increased by 6.5%, and the average sound absorption coefficient of conjugate materials increased by 25.4%, which shows that the increase in the average sound absorption coefficient of conjugate materials is much greater than that of metallic materials. The research shows that studying the sound effects of musical performances based on the acoustic properties of conjugated materials will help explore and develop more immersive and emotionally rich musical experiences.